The dates of the 587/6BCE capture and destruction of Jerusalem - Waard, Henk de (Textus, 2020)
The present article examines the dates of the 587/6BCE capture and destruction of Jerusalem, which differ across the parallel accounts in 2Kgs 24:18–25:21 and Jer 52:1–30. I argue that the Masoretic Text of Jer 52:6 gives the correct date of Jerusalem’s capture, even though the relevant phrase is a later insertion. In addition, I propose a new solution for the problem of the variant dates of the city’s destruction. According to this solution, the original date has been preserved by 2Kgs 25:8, while the date given in Jer 52:12 has been influenced by an incorrect assumption about the date of the capture.